False Negative Carrier Screening in Spinal Muscular Atrophy. (March 2020) - Butcher, Sophie; Smith, Melanie; Woodcock, Ian R.; Delatycki, Martin; Ryan, Monique M.; Forbes, Robin
We describe a case of spinal muscular atrophy diagnosed in an infant despite previous parental carrier testing suggesting low risk of the disease. This case report explains how this situation arose and illustrates that clinicians need to perform diagnostic testing in children where clinical suspicion for spinal muscular atrophy is high, regardless of the result of previous parental carrier testing, because of the risk of false negative results.